2013
DOI: 10.1038/labinvest.2012.160
|View full text |Cite
|
Sign up to set email alerts
|

Delayed preconditioning prevents ischemia/reperfusion-induced endothelial injury in rats: role of ROS and eNOS

Abstract: Ischemic preconditioning (IPC) strongly protects against ischemia/reperfusion (I/R) injury; however, the molecular mechanism involved in delayed preconditioning-induced endothelial protection in peripheral arteries is unknown. Therefore, we examined using functional, morphologic and molecular biologic studies whether delayed IPC decreases formation of reactive oxygen species and upregulates endothelial nitric oxide synthase (eNOS) that in turn contributes to vascular endothelial protection. Adult male Sprague-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…Pretreatment with DMF ameliorated I/RI-induced histological changes, and this effect was attributed to its anti-oxidant efficacy. The observed endothelial dysfunction could be a consequence of decreased synthesis or bioavailability of NO[32]. A previous report showed that the observed endothelial dysfunction is characterized by a marked reduction in NO availability and decreased expression and phosphorylation of eNOS[17].…”
Section: Discussionmentioning
confidence: 99%
“…Pretreatment with DMF ameliorated I/RI-induced histological changes, and this effect was attributed to its anti-oxidant efficacy. The observed endothelial dysfunction could be a consequence of decreased synthesis or bioavailability of NO[32]. A previous report showed that the observed endothelial dysfunction is characterized by a marked reduction in NO availability and decreased expression and phosphorylation of eNOS[17].…”
Section: Discussionmentioning
confidence: 99%
“…NO is important for vascular endothelial cell functional integrity [10][11][12]. Therefore, regulating eNOS expression and increasing NO secretion will be important approaches for vascular endothelial cells protection.…”
Section: Discussionmentioning
confidence: 99%
“…All values were normalized to the household gene gapdh , which is often used in RIPC experiments [91,92] according to the comparative method (2 −ΔΔ C t ). Gapdh mRNA expression levels were stable and were not affected by RIPC treatment.…”
Section: Methodsmentioning
confidence: 99%